1963
DOI: 10.1055/s-0038-1654963
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Factors XII, XI, and IX to Hypercoagulable States

Abstract: SummaryEvidence has been obtained in rabbits that the reduction of the silicone whole blood clotting time to the normal glass range reflects a hypercoagulable state attributable to circulating activated factors XII and XI. The potential clinical implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1963
1963
1975
1975

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We have previously suggested that an increased tendency to thrombus formation, coupled with silicone clotting times in the glass range, represents a hypercoagulable state. 3 The finding of diarrhea and hyperemic intestines suggested the possibility that these rabbits were suffering from a naturally acquired enteritis, which was associated with abnormally shortened clotting times. Evans et al 10 have described a disease of young rabbits characterized by the frequent association of enteritis and polyagglutinable red cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously suggested that an increased tendency to thrombus formation, coupled with silicone clotting times in the glass range, represents a hypercoagulable state. 3 The finding of diarrhea and hyperemic intestines suggested the possibility that these rabbits were suffering from a naturally acquired enteritis, which was associated with abnormally shortened clotting times. Evans et al 10 have described a disease of young rabbits characterized by the frequent association of enteritis and polyagglutinable red cells.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin derived from Escherichia coli 0111:B4 was generously supplied to us by Dr. Herbert A. Ravin, 3 and an endotoxin prepared from Salmonella newington was kindly provided by Dr. P. W. Robbins.…”
Section: Endotoxinmentioning
confidence: 99%
See 2 more Smart Citations
“…The infusion of normal human serum into animals engenders a transient period of hypercoagulability characterized by profound shortening of the whole blood clotting time in both glass and silicone-coated tubes (2). During this period of hypercoagulability, blood trapped in isolated venous segments rapidly coagulates, forming a thrombotic cast of the isolated venous segment (3).…”
mentioning
confidence: 99%